PENGEMBANGAN MODEL PENDIDIKAN KARAKTER DALAM KELUARGA (TINJAUAN PENDIDIKAN KARAKTER BERSPEKTIF ISLAM) - Sarwani Sarwani (Jurnal Ilmu Pemerintahan Widya Praja, 2016)
Development of character education models in the family in the true Islamic perspective departs from the efforts of parents to educate their children by elaborating some models are exempliﬁ ed byeducation experts from a variety of references including how to educate families using the propositionsof Islamic legal sources that exist both Qu’an/Hatits, Ijma friends and Qiyas, so the expectations ofparents to off spring be useful for children religion, homeland and nation can be realized and gets thepleasure of Allah SWT.